Smooth Perturbations to Rényi Entropy - Andrew Buchanan (Journal of High Energy Physics)
Abstract A method is presented for computing the Rényi entropy of a perturbed massless vacuum on the ball via a comparison with lattice field theory. If the perturbed state is Gaussian with smoothly varying correlation functions and the perturbation parameter has units of energy, I show the coefficients for Rényi entropy are analytically computable for all values of the Rényi parameter α in odd dimensions and for integer α in even dimensions. I apply this procedure to compute coefficients for the large distant expansion for the Rényi mutual information of distant balls and the low temperature expansion for the entropy of a thermal field.